Portal vein encasement predicts neoadjuvant therapy response in liver transplantation for perihilar cholangiocarcinoma protocol. (6th August 2015) - Bhat, Mamatha; Hathcock, Matthew; Kremers, Walter K.; Darwish Murad, Sarwa; Schmit, Grant; Martenson, James; Alberts, Steven; Rosen, Charles B.; Gores, Gregory J.; Heimbach, Julie
Summary: Background: Survival and recurrence of cancer after liver transplant (LT) for perihilar cholangiocarcinoma (CCA) following neoadjuvant chemoradiotherapy are strongly correlated with the presence of residual CCA in the liver explant. Aim: To determine factors predicting response to neoadjuvant therapy using the presence of residual CCA on explant as a surrogate marker. Methods: Characteristics of 109 patients having undergone LT for cholangiocarcinoma were abstracted, with attention to parameters hypothesized to influence radiation therapy efficacy. Results: In the multivariable model, the presence of portal vein encasement (OR 11.8; 95% CI: 2.43–57.21; P  = 0.002) and MELD score (OR 1.13; 95% CI: 1.02–1.26; P  = 0.017) were predictive of residual macroscopic disease (c‐statistics 0.78). Oral capecitabine in addition to standard 5‐fluorouracil chemotherapy (OR 0.32, 95% CI: 0.14, 0.71; P  = 0.006) was independently protective against residual cancer, independent of MELD score. Conclusions: Portal vein encasement was strongly predictive of residual macroscopic disease. Radial tumor diameter did not have greater predictive value than longitudinal diameter, confirming the appropriateness of current protocol selection criteria. No particular tumor morphology predicted better response. Maintenance oral capecitabine following 5‐fluorouracil infusion was independently protective against residual disease. Portal vein encasement as a negative prognostic finding should be taken into account to optimize patient selection and management.